Performance Analysis and Model Improvements for Electromagnetic Transient State Estimators - Humberto Cunha de Oliveira; Vinicius Henrique Faria Brito; Jose Carlos de Oliveira; Isaque Nogueira Gondim (IEEE Access)
State estimation techniques for the study of electromagnetic transients use measurement records to analyze the propagation of such effects to other unmonitored locations within an electrical grid. Among the approaches mentioned in the literature, strategies based on numerical derivatives and integrative substitutions stand out because of their implementation facilities and effective responses. However, since these procedures typically rely on simplified component models that omit parameters essential for transient phenomena analysis, inaccurate estimator responses can result. Due to the lack of comparative studies on state estimation methods for electromagnetic transients, this article presents a comparative evaluation of two widely recognized approaches: Numerical Integration Substitution (NIS) and Numerical Derivative Substitution (NDS). In addition, improvements in transformer modeling are proposed for both methods by incorporating previously neglected parameters, such as winding resistances and stray capacitances. Both methods are assessed through computational and experimental simulations, highlighting their performance in terms of accuracy and numerical stability. The results demonstrate that the proposed improvements enhance the estimation accuracy of both methods. Moreover, the improved NDS approach consistently outperforms NIS, exhibiting better convergence under conditions involving high-frequency transients.